Genetic Variability and Correlation for Quantitative Traits of Chickpea Genotypes (Cicer arietinum L.) - Saatu, Madhu; Anakali, Hima Kumar; Akhtar, Shaik Faheem; Bhat, Mohammad Ashraf (International Journal of Bio-resource and Stress Management, 2025)
The present study was conducted using 124 genotypes of chickpea (Cicer arietinum L.) during rabi, 2019–2020 at Regional Research Station, Faculty of Agriculture, Wadura, Sopore, SKUAST-K to assess the variability, correlation among yield and yield contributing traits. The trial was performed by using an Augmented block design. The study included estimates of variability such as genetic variability, phenotypic variability, genotypic coefficient of variability, phenotypic coefficient of variability and inter-relationship among yield and yield contributing traits. The ANOVA estimations showed that there was a significant variation across genotypes for all ten traits investigated in the experiment. The significant magnitude of phenotypic and genotypic coefficient of variation indicated considerable level of variability. Traits such as Plant height, seed yield plant-1, pods plant-1, and days to 50% flowering, all exhibited higher levels of variability whereas Traits like pods plant-1, seeds pod-1 and seed yield plant-1 recorded high genotypic and phenotypic coefficient of variation. The Phenotypic Coefficient of Variation was consistently higher than the Genotypic Coefficient of Variation for all traits. Seed yield plant-1 showed highly significant and correlated positively with pod width, pods plant-1, plant height and days to pod formation. Therefore, these traits could serve as effective selection criteria for genotype improvement in chickpeas because they exhibited high variability. This study would help to identify superior genotypes, leading to the development of high-yielding elite chickpea varieties with desirable characteristics.